2013
DOI: 10.3892/or.2013.2315
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-induced killer cells co-cultured with complete tumor antigen-loaded dendritic cells, have enhanced selective cytotoxicity on carboplatin-resistant retinoblastoma cells

Abstract: Abstract. Retinoblastoma (RB) is a challenging disease that affects mostly young children. Chemical therapy has been shown to have limitations during clinical practice, principally because of the ability of RB to become resistant to the treatment. Nevertheless, chemotherapy is still the main treatment for RB, and immunotherapy has become a promising treatment for most solid tumors with fewer side effects than traditional therapies. In this study, we explored the antitumor effects of cytokine-induced killer (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Immune cells have been cultured in vitro in which they are induced to strongly identify tumor cells before being infused into cancer patients 56 . In vitro cultivation of DCs and Cytokineinduced Killer cells (CIK cells) -a special phenotype of T lymphocyte populations-for cancer treatment has gained increasing research interests 57 . Mononuclear cells were collected and cultured in primary culture supplemented with 10% serum (FBS) to enhance selection of cells capable of adhering to the surface of the flask; this helps to maximize the cells with good adhesion, creating a good cell source for DC differentiation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells have been cultured in vitro in which they are induced to strongly identify tumor cells before being infused into cancer patients 56 . In vitro cultivation of DCs and Cytokineinduced Killer cells (CIK cells) -a special phenotype of T lymphocyte populations-for cancer treatment has gained increasing research interests 57 . Mononuclear cells were collected and cultured in primary culture supplemented with 10% serum (FBS) to enhance selection of cells capable of adhering to the surface of the flask; this helps to maximize the cells with good adhesion, creating a good cell source for DC differentiation 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies reported that immunotherapy is an effective method to lower the recurrence and metastatic rate of malignant tumors due to its high proliferative and cytolytic activity against various types of tumor cells (14,15). Comprehensive immunotherapy treatments aimed at clearing micrometastatic cancer cells may provide highly flexible treatment combinations for cancer (16).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al used CIK cells co-cultured with DCs pulsed with complete retinoblastoma antigens (DCAg). CIK cells showed enhanced differentiation and cytotoxicity even on carboplatin-resistant RB cells; DC-Ag-CIK mixture had little effect on normal retina (Wang et al, 2013c). …”
Section: Cik Cell With Dendritic Cell (Dc)mentioning
confidence: 98%